The Practicality of Applying Physics Learning Games with Scientific Literacy - Poppy Julia Oxana; Hidayati; Renol Afrizon; Rahmat Hidayat (Jurnal Penelitian Pendidikan IPA, 2023)
Physics is part of the natural sciences which plays an essential role in life. Learning physics must be distinct from various learning environments to achieve the stated learning objectives. One of the things that play an essential role, in this case, is the learning media. One of the learning media that can be used is a game. Experts have validated this physics learning game with scientific literacy, but it has yet to be tested for practicality. This study aimed to determine the practicality of implementing physics learning games with scientific literacy for Padang City High School students. This type of research is descriptive, with a sample of students and teachers in six high schools in Padang City, which have been grouped into three levels high, medium, and low. The research instrument used a practical questionnaire with four answer choices. The data analysis used in this research is a descriptive analysis technique. The results showed that the convenience aspect obtained a practicality percentage of 76.76% according to students and 90.63% according to the teacher, the attractiveness aspect obtained a percentage of 79.10% according to students and 86.25% according to teachers, and the last aspect of efficiency obtained a percentage of 79. 43% according to students and 92.50% according to teachers. Overall, according to the students, this game is practical to use, with a percentage of 78.43%. According to the teacher, the game has a percentage of 90.63%, with a very practical category.